2018
DOI: 10.21037/jtd.2017.10.125
|View full text |Cite
|
Sign up to set email alerts
|

The pathological and molecular diagnosis of malignant pleural mesothelioma: a literature review

Abstract: on the application of a panel including positive (mesothelial-related) and negative markers with greater than 80% sensitivity and specificity, which need to be selected based on morphology and clinical information.Moreover, in challenging cases, fluorescent in situ hybridization (FISH) testing for the p16 deletion and IHC to evaluate the loss of BRCA1-associated protein 1 (BAP1) expression could be useful in distinguishing benign from malignant pleural proliferations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 61 publications
0
45
0
Order By: Relevance
“…The epithelioid subtype is the most common (60–80%) and has the best prognosis with an OS of 13.1 months. The sarcomatoid subtype, on the other hand, has the worst prognosis with an OS of 4–6 months [60]. MPE occurs in 54–90% of all malignant pleural mesothelioma cases and forms at an early stage [21,61,62].…”
Section: Cancer and Malignant Pleural Effusionmentioning
confidence: 99%
“…The epithelioid subtype is the most common (60–80%) and has the best prognosis with an OS of 13.1 months. The sarcomatoid subtype, on the other hand, has the worst prognosis with an OS of 4–6 months [60]. MPE occurs in 54–90% of all malignant pleural mesothelioma cases and forms at an early stage [21,61,62].…”
Section: Cancer and Malignant Pleural Effusionmentioning
confidence: 99%
“…Global incidence of MPM has risen steadily over the past decade, and it is predicted to reach the highest peak in 2020 (1,2). MPM is a heterogeneous tumor, including three main histological subtypes: Epithelioid (60-80%), sarcomatoid (<10%) and mixed (10-15%) (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, the differential diagnosis of MPM and benign pleural lesions is a hard task to accomplish, and currently the only criterion to certainly determine the malignancy is the presence of stromal or lung invasion (5). However, it is not always possible to estimate whether stromal invasion is present or not, according to quantitative and qualitative parameters of pleural biopsies and their representativeness of the whole lesion (4). Moreover, for many patients pleural biopsies are not available and diagnosis has to be made on cytological specimens from pleural effusions, whose diagnostic sensitivity is variable ranging from 20 to 70% (6).…”
Section: Introductionmentioning
confidence: 99%
“…Malignant mesothelioma is a fatal tumor caused by exposure to asbestos 13 . The absence of mesothelioma-specific markers has often made it difficult to diagnose malignant mesothelioma 14 . In our previous study 15 , we identified the sialylated protein HEG homolog 1 (HEG1) as a novel and precise mesothelioma marker.…”
Section: Introductionmentioning
confidence: 99%